Highly Efficient Palladium-Catalyzed Arsination on the Way to Arsine Ligands - Martín, Sandra Elizabeth (2011)
Since arsines are drawing particular attention as ligands in metal-catalyzed reactions, the development of new methods to obtain organoarsines is increasingly recognized as central in the synthesis of new ligands. Transition metal-catalyzed reactions with organoheteroatom compounds are widely used to acquire different heteroatom-contained compounds. This article reviews a highly efficient one-pot, two-step Pd-catalyzed arsination with n-Bu3SnAsPh2 and diverse electrophiles. The cross-coupling reactions of these stannanes with ArI afforded the functionalized triarylarsines, and with RfI as electrophiles new perfluoroalkylarsines were achieved. By following this methodology, a biphenyl arsine ligand was acquired. The use of the commercially available, air-stable, and inexpensive AsPh3 as the initial reagent and the one-pot process make this methodology a useful approach to obtaining a wide range of organoarsines.